Primary osseous tumours of the elbow: 60 years of registry experience. Issue 4 (October 2015) - Halai, Mansur; Gupta, Sanjay; Spence, Stephanie; Wallace, David; Rymaszewski, Lech; Mahendra, Ashish
Background: We present the largest series of surgically treated primary bone tumours of the elbow in the English literature (75 cases). We sought to identify characteristics specific to these lesions and recommend an investigatory protocol. Methods: The national registry and case notes were reviewed between 1954-2014. Tumours were classified according to Enneking's spectrum. Results: There were no benign latent cases in this series as these were managed locally. All patients presented with persistent rest pain, with or without swelling. The distal humerus, in contrast to the proximal radius and ulna, was responsible for the majority and the more aggressive cases. Misdiagnosis was evident in 13% of cases; most of which were attributed to simple bone cysts. All patients that were referred required surgical intervention to either establish the diagnosis or for treatment. Benign tumours had a 19% recurrence rate, with giant cell tumour the most aggressive. Malignant tumours carried 39% local recurrence rate and a 5-year mortality of 61%. Conclusions: The suspicion of a tumour should be raised in the patient with unremitting, unexplained, non-mechanical bony elbow pain. These echo the NICE recommendations and we recommend prompt specialist referral. With high rates of local recurrence, we recommend close postoperative monitoring.